Accuracy of UAV Photogrammetry in Glacial and Periglacial Alpine Terrain: A Comparison With Airborne and Terrestrial Datasets - Groos, Alexander Raphael; Aeschbacher, Reto; Fischer, Mauro; Kohler, Nadine; Mayer, Christoph; Senn-Rist, Armin (Frontiers in Remote Sensing, 2022)
Unoccupied Aerial Vehicles (UAVs) equipped with optical instruments are increasingly deployed in high mountain environments to investigate and monitor glacial and periglacial processes. The comparison and fusion of UAV data with airborne and terrestrial data offers the opportunity to analyse spatio-temporal changes in the mountains and to upscale findings from local UAV surveys to larger areas. However, due to the lack of gridded high-resolution data in alpine terrain, the specific challenges and uncertainties associated with the comparison and fusion of multi-temporal data from different platforms in this environment are not well known. Here we make use of UAV, airborne, and terrestrial data from four (peri)glacial alpine study sites with different topographic settings. The aim is to assess the accuracy of UAV photogrammetric products in complex terrain, to point out differences to other products, and to discuss best practices regarding the fusion of multi-temporal data. The surface geometry and characteristic geomorphological features of the four alpine sites are well captured by the UAV data, but the positional accuracies vary greatly. They range from 15 cm (root-mean-square error) for the smallest survey area (0.2 km2) with a high ground control point (GCP) density (40 GCPs km−2) to 135 cm for the largest survey area (>" role="presentation">>2.5 km2) with a lower GCP density (<" role="presentation"><10 GCPs km−2). Besides a small number and uneven distribution of GCPs, a low contrast, and insufficient lateral image overlap (<" role="presentation"><50–70%) seem to be the main causes for the distortions and artefacts found in the UAV data. Deficiencies both in the UAV and airborne data are the reason for horizontal deviations observed between the datasets. In steep terrain, horizontal deviations of a few decimetres may result in surface elevation change errors of several metres. An accurate co-registration and evaluation of multi-temporal UAV, airborne, and terrestrial data using tie points in stable terrain is therefore of utmost importance when it comes to the investigation of surface displacements and elevation changes in the mountains. To enhance the accuracy and quality of UAV photogrammetry, the use of UAVs equipped with multi-spectral cameras and high-precision positioning systems is recommended, especially in rugged terrain and snow-covered area
Keywords: Alps; cryosphere; drone survey; data fusion; glacier monitoring; orthophoto; DSM; OpenDroneMap

A first attempt to model region-wide glacier surface mass balances in the Karakoram: findings and future challenges - Groos, Alexander Raphael; Mayer, Christoph; Smiraglia, Claudio; Diolaiuti, Guglielmina; Lambrecht, Astrid (Geografia Fisica E Dinamica Quaternaria, 2017)

A low-cost and open-source approach for supraglacial debris thickness mapping using UAV-based infrared thermography - Messmer, Jérôme; Groos, Alexander Raphael (Cryosphere, 2024)
Debris-covered glaciers exist in many mountain ranges and play an important role in the regional water cycle. However, modelling the surface mass balance, runoff contribution and future evolution of debris-covered glaciers is fraught with uncertainty as accurate observations on small-scale variations in debris thickness and sub-debris ice melt rates are only available for a few locations worldwide. Here we describe a customised low-cost unoccupied aerial vehicle (UAV) for high-resolution thermal imaging of mountain glaciers and present a complete open-source pipeline that facilitates the generation of accurate surface temperature and debris thickness maps from radiometric images. First, a radiometric orthophoto is computed from individual radiometric UAV images using structure-from-motion and multi-view-stereo techniques. User-specific calibration and correction procedures can then be applied to the radiometric orthophoto to account for atmospheric and environmental influences that affect the radiometric measurement. The thermal orthophoto reveals distinct spatial variations in surface temperature across the surveyed debris-covered area. Finally, a high-resolution debris thickness map is derived from the corrected thermal orthophoto using an empirical or inverse surface energy balance model that relates surface temperature to debris thickness and is calibrated against in situ measurements. Our results from a small-scale experiment on the Kanderfirn (also known as Kander Neve) in the Swiss Alps show that the surface temperature and thickness of a relatively thin debris layer (ca. 0–15 cm) can be mapped with high accuracy using an empirical or physical model. On snow and ice surfaces, the mean deviation of the mapped surface temperature from the melting point (∼ 0 ∘C) was 0.6 ± 2.0 ∘C. The root-mean-square error of the modelled debris thickness was 1.3 cm. Through the detailed mapping, typical small-scale debris features and debris thickness patterns become visible, which are not spatially resolved by the thermal infrared sensors of current-generation satellites. The presented approach paves the way for comprehensive high-resolution supraglacial debris thickness mapping and opens up new opportunities for more accurate monitoring and modelling of debris-covered glacier

An hourly ground temperature dataset for 16 high-elevation sites (3493–4377 m a.s.l.) in the Bale Mountains, Ethiopia (2017–2020) - Groos, Alexander Raphael; Niederhauser, Janik; Lemma, Bruk; Fekadu, Mekbib; Zech, Wolfgang; Haensel, Falk; Wraase, Luise; Akçar, Naki; Veit, Heinz (Earth System Science Data, 2022)
Tropical mountains and highlands in Africa are under pressure because of anthropogenic climate and land-use change. To determine the impacts on the afro-alpine environment and to assess the potential socio-economic consequences, the monitoring of essential climate and environmental variables at high elevation is fundamental. However, long-term temperature observations on the African continent above 3000 m are very rare. Here we present a consistent multiannual dataset of hourly ground temperatures for the Bale Mountains in the southern Ethiopian Highlands, which comprise Africa's largest tropical alpine area. The dataset covers the period from January 2017 to January 2020. To characterise and continuously monitor the mountain climate and ecosystem of the Bale Mountains along an elevation gradient from 3493 to 4377 m, ground temperature data loggers have been installed at seven sites at 2 cm depth; at four sites at 10 cm depth; and at five sites at 2, 10, and 50 cm depth. The statistical analysis of the generated time series reveals that ground temperatures in the Bale Mountains are subject to large daily fluctuations of up to 40 ∘C and minor seasonal variations on the order of 5 to 10 ∘C. Besides incoming short-wave radiation, ground moisture, and clouds at night, slope orientation and the type of vegetation coverage seem to be the main factors controlling daily and seasonal ground temperature variations. On the central Sanetti Plateau above 3800–4000 m, the mean annual ground temperature ranges from 9 to 11 ∘C. However, nocturnal ground frost down to a depth of 5 cm occurs frequently during the dry season from November to February. At the five sites where ground temperature is measured at three depths, the monitoring will be continued to trace long-term changes. To promote the further use of the ground temperature dataset by the wider research community dealing with the climate and geo-ecology of tropical mountains in eastern Africa, it is made freely available via the open-access repository Zenodo: https://doi.org/10.5281/zenodo.6047457 (Groos et al., 2022).<br

A regional assessment of the deglaciation history of the Swiss Plateau based on newly obtained and re-evaluated Be-10 cosmic-ray exposure ages - Hofmann, Felix Martin; Groos, Alexander Raphael; Garcia Morabito, Ezequiel; Struck, Julian; Gnägi, Christian; Scharf, Andreas; Rugel, Georg; Merchel, Silke; Zech, Roland (Quaternary Science Advances, 2023)
During marine oxygen isotope stage (MIS) 2, the Swiss Plateau temporarily hosted large piedmont lobe glaciers that retreated after their maximum advance back to the fringe of the Alps. The presence of moraines in this region indicates that overall glacier recession was punctuated by repeated phases of ice-marginal stability and re-advances. The timing of these events in the region formerly covered by the eastern lobe of the Rhône (or Valais) glacier has been controversial and remains poorly constrained due to the lack of chronological data. To fill this gap, 10 Be cosmic-ray exposure (CRE) dating was applied to erratic boulders inside the assumed MIS 2 maximum extent of this piedmont lobe. An erratic boulder at an ice-marginal position upstream from the suspected MIS 2 maximum extent gave an age of about 19 ka. Erratic boulders at a presumably younger ice-marginal position (Brästenberg position) yielded an average age of ca. 20 ka. However, several erratic boulders beyond the Brästenberg position gave internally consistent, but stratigraphically too young ages of ca. 17 ka. We cannot rule out that glacier recession from the Brästenberg position began no later than 17 ka. CRE dating of a moraine of a presumably younger ice-marginal position (Solothurn position) gave unrealistically old ages and an incredibly young age (86 ka, 40 ka, and 4 ka). Carbon-14 CRE dating should be applied to provide additional information on the last deglaciation of the Swiss Plateau. Nevertheless, despite outlying ages, the presented chronological data contribute to an overall consistent and increasingly refined chronology of the last deglaciation of the Swiss Plateau when compared with 59 previously published CRE ages.<br
Keywords: Terrestrial in situ cosmogenic nuclides; Exposure dating; Moraine; Erratic boulder; Swiss Plateau; Deglaciation; Glacier fluctuations

Frequency of low clouds in taiwan retrieved from MODIS data and its relation to cloud forest occurrence - Thies, Boris; Groos, Alexander Raphael; Schulz, Martin; Li, Ching-Feng; Chang, Shih-Chieh; Bendix, Jörg (Remote Sensing, 2015)
The relationship between satellite-derived low cloud frequency and the occurrence of tropical montane cloud forest (TMCF) in Taiwan was investigated. From daily MODIS cloud mask products between 2003 and 2012 the low cloud class was extracted and mean low cloud frequency was calculated for Taiwan. This low cloud frequency map was blended with an existing plot-based vegetation classification for Taiwan to analyze the relationship between low cloud frequency and TMCF occurrence. Receiver operating characteristics curves and the area under the ROC curve (AUC) were used to analyze if a relationship exists. No relationship was found for all four TMCF types taken together (AUC = 0.61) and for the dominant TMCF type, Quercus montane evergreen broad-leaved cloud forest (AUC = 0.5). Strong relationships were found for the two spatially-restricted TMCF types, Fagus montane deciduous broad-leaved cloud forest (AUC = 0.91) and Pasania- Elaeocarpus montane evergreen broad-leaved forest (AUC = 0.84), as well as for the second dominant type Chamaecyparis montane mixed cloud forest (AUC = 0.74). The results show that low cloud frequency thresholds might be associated with specific cloud forest types in Taiwan. Further studies should incorporate information about cloud base height, cloud density, and cloud immersion time as well as satellite-based cloud frequency information with a higher temporal resolution. Combination with satellite-based land cover classifications for Taiwan would allow quasi-continuous observation of TMCF changes. Such knowledge would be the precondition for effective protective actions concerning this exceptional but threatened ecosystem.
Created from Fastlane, Scopus look-up
Keywords: MODIS; Satellite; Taiwan; Tropical montane cloud forest; Vegetation survey

Middle Stone Age foragers resided in high elevations of the glaciated Bale Mountains, Ethiopia - Ossendorf, Goetz; Groos, Alexander R.; Bromm, Tobias; Tekelemariam, Minassie Girma; Glaser, Bruno; Lesur, Josephine; Schmidt, Joachim; Akcar, Naki; Bekele, Tamrat; Beldados, Alemseged; Demissew, Sebsebe; Kahsay, Trhas Hadush; et al. (Science, 2019)
Studies of early human settlement in alpine environments provide insights into human physiological, genetic, and cultural adaptation potentials. Although Late and even Middle Pleistocene human presence has been recently documented on the Tibetan Plateau, little is known regarding the nature and context of early persistent human settlement in high elevations. Here, we report the earliest evidence of a prehistoric high-altitude residential site. Located in Africa’s largest alpine ecosystem, the repeated occupation of Fincha Habera rock shelter is dated to 47 to 31 thousand years ago. The available resources in cold and glaciated environments included the exploitation of an endemic rodent as a key food source, and this played a pivotal role in facilitating the occupation of this site by Late Pleistocene hunter-gatherers.
Created from Fastlane, Scopus look-up

Nonuniform late pleistocene glacier fluctuations in tropical Eastern Africa - Groos, Alexander R.; Akçar, Naki; Yesilyurt, Serdar; Miehe, Georg; Vockenhuber, Christof; Veit, Heinz (Science Advances, 2021)
Today's ice caps and glaciers in Africa are restricted to the highest peaks, but during the Pleistocene, several mountains on the continent were extensively glaciated. However, little is known about regional differences in the timing and extent of past glaciations and the impact of paleoclimatic changes on the afro-alpine environment and settlement history. Here, we present a glacial chronology for the Ethiopian Highlands in comparison with other East African Mountains. In the Ethiopian Highlands, glaciers reached their maximum 42 to 28 ka thousand years ago before the global Last Glacial Maximum. The local maximum was accompanied by a temperature depression of 4.4° to 6.0°C and a 700-m downward shift of the afro-alpine vegetation belt, reshaping the human and natural habitats. The chronological comparison reveals that glaciers in Eastern Africa responded in a nonuniform way to past climatic changes, indicating a regionally varying influence of precipitation, temperature, and orography on paleoglacier dynamics.
Created from Fastlane, Scopus look-up

The enigma of relict large sorted stone stripes in the tropical Ethiopian Highlands - Groos, Alexander R.; Niederhauser, Janik; Wraase, Luise; Haensel, Falk; Nauss, Thomas; Akçar, Naki; Veit, Heinz (Earth Surface Dynamics, 2021)
Large forms of sorted patterned ground belong to the most prominent geomorphic features of periglacial and permafrost environments of the mid-latitudes and polar regions, but they were hitherto unknown in the tropics. Here, we report on relict large sorted stone stripes (up to 1000m long, 15m wide, and 2m deep) on the ca. 4000m high central Sanetti Plateau of the tropical Bale Mountains in the southern Ethiopian Highlands. These geomorphic features are enigmatic since forms of patterned ground exceeding several metres are commonly associated with distinct seasonal ground temperatures, oscillating around 0 °C. To systematically investigate present frost phenomena and relict periglacial landforms in the Bale Mountains, we conducted extensive geomorphological mapping. The sorted stone stripes were studied in more detail by applying aerial photogrammetry, ground-penetrating radar measurements, and 36Cl surface exposure dating. In addition, we installed ground temperature data loggers between 3877 and 4377m to analyse present frost occurrence and seasonal ground temperature variations. Superficial nocturnal ground frost was measured at 35-90 d per year, but the ground beneath the upper few centimetres remains unfrozen the entire year. Seasonal frost occurrence would require a mean annual ground temperature depression of about 11 °C, corresponding to an air temperature decrease of about 6-8 °C (relative to today) as inferred from a simple statistical ground temperature model experiment. Our results suggest the formation of the large sorted stone stripes under past periglacial conditions related to lateral and vertical frost sorting in the course of cyclic freezing and thawing of the ground. It is likely that the stone stripes formed either in proximity to a former ice cap on the Sanetti Plateau over the last glacial period due to seasonal frost heave and sorting or they developed over multiple cold phases during the Pleistocene. Although certain aspects of the genesis of the large sorted stone stripes remain unresolved, the presence of these geomorphic features provides independent evidence besides glacial landforms for unprecedented palaeoclimatic and palaeoenvironmental changes in the tropical Bale Mountains during the (Late) Pleistocene.
Created from Fastlane, Scopus look-up

The potential of low-cost UAVs and open-source photogrammetry software for high-resolution monitoring of alpine glaciers: A case study from the kanderfirn (Swiss Alps) - Groos, Alexander R.; Bertschinger, Thalia; Kummer, Céline; Erlwein, Sabrina; Munz, Lukas; Philipp, Andreas (Geosciences, 2019)
Unmanned Aerial Vehicles (UAV) are a rapidly evolving tool in geosciences and are increasingly deployed for studying the dynamic processes of the earth's surface. To assess the potential of autonomous low-cost UAVs for the mapping and monitoring of alpine glaciers, we conducted multiple aerial surveys on the Kanderfirn in the Swiss Alps in 2017 and 2018 using open hardware and software of the Paparazzi UAV project. The open-source photogrammetry software OpenDroneMap was tested for the generation of high-resolution orthophotos and digital surface models (DSMs) from aerial imagery and cross-checked with the well-established proprietary software Pix4D. Accurately measured ground control points served for the determination of the geometric accuracy of the orthophotos and DSMs. A horizontal (xy) accuracy of 0.7-1.2 m and a vertical (z) accuracy of 0.7-2.1 m was achieved for OpenDroneMap, compared to a xy-accuracy of 0.3-0.5 m and a z-accuracy of 0.4-0.5 m obtained for Pix4D. Based on the analysis and comparison of different orthophotos and DSMs, surface elevation, roughness and brightness changes from 3 June to 29 September 2018 were quantified. While the brightness of the glacier surface decreased linearly over the ablation season, the surface roughness increased. The mean DSM-based elevation change across the glacier tongue was 8 m, overestimating the measured melting and surface lowering at the installed ablation stakes by about 1.5 m. The presented results highlight that self-built fixed-wing UAVs in tandem with open-source photogrammetry software are an affordable alternative to commercial remote-sensing platforms and proprietary software. The applied low-cost approach also provides great potential for other regions and geoscientific disciplines.
Created from Fastlane, Scopus look-up
Keywords: Digital elevation models; Glacier dynamics; Glacier monitoring; OpenDroneMap; Orthophotos; Paparazzi UAV; Photogrammetry; Structure from motion; Unmanned Aerial Vehicles